Inherent Proton Conduction in a 2D Coordination Framework - Umeyama, Daiki; Horike, Satoshi; Inukai, Munehiro; Itakura, Tomoya; Kitagawa, Susumu (Journal of the American Chemical Society, 2012)
We synthesized a coordination polymer consisting of Zn2+, 1,2,4-triazole, and orthophosphates, and demonstrated for the first time intrinsic proton conduction by a coordination network. The compound has a two-dimensional layered structure with extended hydrogen bonds between the layers. It shows intrinsic proton conductivity along the direction parallel to the layers, as elucidated by impedance studies of powder and single crystals. From the low activation energy for proton hopping, the conduction mechanism was found to be of the Grotthuss fashion. The hopping is promoted by rotation of phosphate ligands, which are aligned on the layers at appropriate intervals.